2011
DOI: 10.1098/rsif.2011.0547
|View full text |Cite
|
Sign up to set email alerts
|

Secreted, receptor-associated bone morphogenetic protein regulators reduce stochastic noise intrinsic to many extracellular morphogen distributions

Abstract: Morphogens are secreted molecules that specify cell-fate organization in developing tissues. Patterns of gene expression or signalling immediately downstream of many morphogens such as the bone morphogenetic protein (BMP) decapentaplegic (Dpp) are highly reproducible and robust to perturbations. This contrasts starkly with our expectation of a noisy interpretation that would arise out of the experimentally determined low concentration (approximately picomolar) range of Dpp activity, tight receptor binding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…This result supports a previous assumption made in [4] where the recruitment of Type II receptor was excluded to simplify the modeling steps while characterizing the noise profile of a SBP regulated BMP signaling system.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result supports a previous assumption made in [4] where the recruitment of Type II receptor was excluded to simplify the modeling steps while characterizing the noise profile of a SBP regulated BMP signaling system.…”
Section: Introductionsupporting
confidence: 90%
“…The parameter screen on the intermediate dynamics yields three primary qualitative subclasses for Cv-2 behavior in regulation of extracellular BR (C) fluctuation amplitude: i) reduced amplitude ii) increased amplitude and iii) mixed amplitude behavior [4]. Three primary types of responses of Cv-2 action on BMP fluctuations are shown in Figure 2a-c.…”
Section: Methodsmentioning
confidence: 99%
“…Mathematical models concerning BMP signalling mainly focused on receptor dynamics [30] or steady-state behaviour of mutual-inhibition loops [23]. However, temporal dynamics of the BMP signalling network including intracellular molecules and its role in noise attenuation have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In other work on the same network, Karim et al modeled the local receptor/ligand/ Cv-2 interactions and found that Cv-2 imparts signaling robustness to small levels of BMP ligand and overcomes the slow receptor dynamics, which leads to a high fidelity interpretation of the extracellular gradient over time (Karim et al 2012). In this model, Cv-2 significantly reduces signaling noise, leading to a more reliable interpretation of position and a sharper, more reliable boundary.…”
Section: Discovering Mechanisms: Patterning In the Drosophila Embryomentioning
confidence: 99%